Focus Country: Kenya (EdTech Hub)
Kenya Focus country EdTech Hub works in six focus countries (Bangladesh, Ghana, Kenya, Pakistan, Sierra Leone and Tanzania) to conduct research, support governments, and support scale-up of EdTech programmes.   “Female students with teacher on computer” by Ericsson Images is licensed under CC BY-NC-ND 2.0 READ KENYA COUNTRY SCAN Population: 47.6 million Median age: 20 years Internet penetration: 43% Mobile penetration:…